Membentuk Perilaku Aman Bekerja dengan Menganalisa Komunikasi Internal dalam Mengedukasi K3 di PT XYZ - Gina Wardhani; Mochammad Kresna Noer (IAI Nasional Laa Roiba Bogor, 2026)
The complexity of the production process, the use of heavy equipment, and working conditions in the field demand the strict implementation of Occupational Health and Safety (OHS) systems in the mining industry. Unsafe behavior from workers is the leading cause of accidents. PT. XYZ has shown good performance in workplace safety, as evidenced by various awards in the field of occupational safety. However, it is important to understand that this success is not only determined by systems and policies but also by the communication processes that occur within the organization. Based on this, this study aims to analyze internal communication in the internal communication process applied by PT XYZ to shape safe working behavior. This study uses a descriptive qualitative method with data collection techniques through in-depth interviews with several key informants. The research results show that out of 22 key informants, it was found that communication is carried out through various formal and informal channels, such as toolbox meetings, safety talks, pre-start meetings, safety briefings, OHS training, safety alerts, safety posters, digital media, as well as direct communication by supervisors and OHS practitioners in the field. Communication doesn't just happen vertically from management to workers, but also horizontally and diagonally through coordination among employees, supervisors, and relevant departments. This shows that internal communication is an important part of implementing a safety culture in the company. So, the goal of internal communication in supporting OHS implementation and building a safety culture in the company has been achieved well, even though some aspects of its execution still need improvement.